Antifungal Agents for the Treatment of Systemic Fungal Infections in Children - UD Allen (Canadian Journal of Infectious Diseases and Medical Microbiology)
Traditionally, the mainstay of systemic antifungal therapy has been amphotericin B deoxycholate (conventional amphotericin B). Newer agents have been developed to fulfill special niches and to compete with conventional amphotericin B by virtue of having more favourable toxicity profiles. Some agents have displaced conventional amphotericin B for the treatment of specific fungal diseases. For example, voriconazole has emerged as the preferred treatment for invasive pulmonary aspergillosis. This notwithstanding, conventional amphotericin B remains a useful agent for the treatment of paediatric fungal infections. Knowledge of the characteristics of the newer agents is important, given the increasing numbers of patients who are being treated with these drugs. Efforts need to be directed at research aimed at generating paediatric data where these are lacking. The antifungal agents herein described are most often used as monotherapy regimens because there is no uniform consensus on the value of combination therapy, except for specific scenarios.